Titania‐Based Spherical Mie Resonators Elaborated by High‐Throughput Aerosol Spray: Single Object Investigation. (31st May 2018) - Checcucci, Simona; Bottein, Thomas; Claude, Jean‐Benoit; Wood, Thomas; Putero, Magali; Favre, Luc; Gurioli, Massimo; Abbarchi, Marco; Grosso, David
Abstract: In the framework of photonics with all‐dielectric nanoantennas, sub‐micrometric spheres can be exploited for a plethora of applications including vanishing back‐scattering, enhanced directivity of a light emitter, beam steering, and large Purcell factors. Here, the potential of a high‐throughput fabrication method based on aerosol‐spray is shown to form quasi‐perfect sub‐micrometric spheres of polycrystalline TiO2 . Spectroscopic investigation of light scattering from individual particles reveals sharp resonances in agreement with Mie theory, neat structural colors, and a high directivity. Owing to the high permittivity and lossless material in use, this method opens the way toward the implementation of isotropic meta‐materials and forward‐directional sources with magnetic responses at visible and near‐UV frequencies, not accessible with conventional Si‐ and Ge‐based Mie resonators. Abstract : Crystalline Titania‐based sub‐micrometric spheres are prepared by high‐throughput aerosol‐spray and their Mie resonances properties are carefully investigated. Light scattering from individual particles reveals sharp resonances and neat structural colors. Owing to the high permittivity and lossless of the material in use, this method opens the way toward the implementation of isotropic metamaterials and forward‐directional sources at visible and near‐UV frequencies.